Preparation, analysis and applications of rubber seed oil and its derivatives in surface coatings - Aigbodion A I; Pillai C K S
Rubber seed oil(RSO) was used in the manufacture of alkyd resins (both solvent and waterborne) which were evaluated as binders in air-drying binder in surface coatings. Heating conferred drying ability on the crude RSO that was naturally semi-drying. The physicochemical properties of solvent-borne alkyds were shown to vary with oil length (OL) and they were optimum at 50;OL. Water-bone alkyds investigated showed that the sample with lower oil content contained lower volatile organic content. All the alkyd samples and heated RSO were fairly resistant to water and alkali, while they were virtually unaffected by acid abd salt solutions. The water-borne alkyds were, however, more resistant than their solvent-borne counterparts, but exhibited lower scratch/gouge pencil hardness.
Keywords: Alkyd resins; Rubber seed oil; Surface coatings; Water resistance